Randomized Phase II Trial of Carboplatin-Paclitaxel Versus Carboplatin-Paclitaxel-Trastuzumab in Uterine Serous Carcinomas That Overexpress Human Epidermal Growth Factor Receptor 2/neu - Fader, Amanda N; Roque, Dana M; Siegel, Eric; Buza, Natalia; Hui, Pei; Abdelghany, Osama; Chambers, Setsuko K; Secord, Angeles Alvarez; Havrilesky, Laura; O'Malley, David M; Backes, Floor; Nevadunsky, Nicole; et al. (Journal of clinical oncology, 2018)
Purpose Uterine serous carcinoma is a rare, aggressive variant of endometrial cancer. Trastuzumab is a humanized monoclonal antibody that targets human epidermal growth factor receptor 2 (HER2)/neu, a receptor overexpressed in 30% of uterine serous carcinoma. This multicenter, randomized phase II trial compared carboplatin-paclitaxel with and without trastuzumab in patients with advanced or recurrent uterine serous carcinoma who overexpress HER2/neu. Methods Eligible patients had primary stage III or IV or recurrent HER2/neu-positive disease. Participants were randomly assigned to receive carboplatin-paclitaxel (control arm) for six cycles with or without intravenous trastuzumab (experimental arm) until progression or unacceptable toxicity. The primary end point was progression-free survival, which was assessed for differences between treatment arms via one-sided log-rank tests. Results From August 2011 to March 2017, 61 patients were randomly assigned. Forty progression-free survival-related events occurred among 58 evaluable participants. Among all patients, median progression-free survival was 8.0 months (control) versus 12.6 months (experimental; P = .005; hazard ratio [HR], 0.44; 90% CI, 0.26 to 0.76). Similarly, median progression-free survival was 9.3 (control) versus 17.9 (experimental) months among 41 patients with stage III or IV disease undergoing primary treatment ( P = .013; HR, 0.40; 90% CI, 0.20 to 0.80) and 6.0 (control) versus 9.2 months (experimental), respectively, among 17 patients with recurrent disease ( P = .003; HR, 0.14; 90% CI, 0.04 to 0.53). Toxicity was not different between treatment arms, and no unexpected safety signals emerged. Conclusion Addition of trastuzumab to carboplatin-paclitaxel was well tolerated and increased progression-free survival. These encouraging results deserve further investigation to determine their impact on overall survival in patients with advanced or recurrent uterine serous carcinoma who overexpress HER2/neu.